Artificial Light at Night: A New Challenge in Microphytobenthos Research - Maggi, Elena; Serôdio, João (Frontiers in Marine Science, 2020)
Artificial light at night (ALAN) has been recently recognized as a globally widespread anthropogenic disturbance, characterized by different intensities and spectra, as well as spatial and temporal variability. Among marine organisms, those living on coastal areas are particularly exposed to artificial light. Some recent studies anticipated a potential for influences of ALAN on microphytobenthos (MPB) on rocky shores, either direct or indirectly mediated by trophic relationships. Here we emphasize the need for further investigations in different habitats, as well as on synergistic interferences with other stressors already impinging on coastal areas. The study of effects of ALAN poses new challenges in MPB research, including those related to the use of instruments for measuring both the light environment and the functioning of microbial photoautotrophs at night, and to the development of common monitoring approaches and manipulative experiments.